Implementation of the Singing Method in Arabic Language Tutoring (LEBAR) for Children in Ciririp Village, Panyingkiran Hamlet, Purwakarta - Risma Diyaul Aulia; Dede Rizal Munir; Tb Abdul Hamid (Yayasan Daarul Huda Kruengmane, 2026)
Vocabulary mastery (mufradat) is a fundamental component in learning Arabic. However, children in Ciririp Village face environmental challenges, as the language is neither used in daily communication nor taught in formal schools. This community service program aimed to implement the singing method as an enjoyable learning strategy to improve basic Arabic vocabulary mastery among elementary school–aged children. The program was conducted through an Arabic tutoring initiative (LEBAR) over six meetings from January 23 to February 2, 2026, at the Al-Hidayah Mosque Hall in Panyingkiran, involving 15 students. The learning materials focused on daily vocabulary such as greetings, body parts, family members, and simple conjunctions, which were delivered through educational songs. Observations indicated high enthusiasm and active participation among the students during the learning process, while evaluation through picture-based exercises revealed improvement in their ability to recognize, memorize, and pronounce vocabulary. The findings demonstrate that the singing method effectively creates a positive learning environment, reduces anxiety, and strengthens long-term memory of Arabic vocabulary among children in non-Arabic-speaking areas. Therefore, it can serve as an innovative and contextual alternative approach to language learning.